Terminological Shifts: Mass Media or Mass Communication Media? - Avetisyan, Yuri (Bulletin of Yerevan University B: Philology, 2026)
In the contemporary Armenian media landscape, the replacement of the component լրատվություն (“information”) in the term ԶԼՄ (զանգվածային լրատվության միջոցներ — mass media) with the term հաղորդակցություն (“communication”), that is, the shift to ԶՀՄ (զանգվածային հաղորդակցության միջոցներ — means of mass communication), is caused by structural and functional transformations of the system, as well as by the factors that have triggered these transformations. The term communication implies not merely—or not only—one-way transmission of information, but communicative interaction involving the active participation of the audience and processes of perception and interpretation (a functional shift). The concept of mass communication encompasses not only the classical information media (the print press, radio, television, news agencies), taking into account the changes they have undergone, but also new online communication platforms (electronic press, communication tools in social networks, etc.), thus reflecting structural changes. In contemporary scholarly discourse, the term communication predominates in international practice. From a strictly linguistic perspective, due to the semantic and functional inadequacy of the term information, the communicative role of the media is either ignored or, at the very least, relegated to the background (terminological normalization). Today, the disciplinary study of media is no longer confined to journalism alone: media are also examined within communication theory, sociolinguistics, discourse analysis, cultural studies, and other fields (a methodological argument). In Armenian media linguistics, the term mass media is preferred when referring to traditional media institutions. In all other cases, it is advisable to use means of mass communication. The term media has not yet acquired a standardized equivalent in Armenian and is employed as needed; time will clarify both its status and its sphere of usage.